Magma Chamber Model of Batur Caldera, Bali, Indonesia: Compositional Variation of Two Facies, Large-Volume Dacitic Ignimbrites - Sutawidjaja, Igan S.; Rosana, Mega F.; Watanabe, K. (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.2.111-124Batur is one of the finest known calderas on Earth, and is the source of at least two major ignimbrite eruptions with a combined volume of some 84 km3 and 19 km3. These ignimbrites have a similar compositions, raising the question of whether they are geneticaly related. The Batur Ignimbrite-1 (BI-1) is crystal poor, containing rhyodacitic (68 - 70wt % SiO2), white to grey pumices and partly welded and unwelded. The overlying Batur Ignimbrite-2 (BI-2) is a homogeneous grey to black dacitic pumices (64 - 66 wt % SiO2), unwelded and densely welded (40 - 60% vesicularity), crystal and lithic rich. Phase equilibria indicate that the Batur magma equilibrated at temperatures of 1100 - 1300oC with melt water contents of 3 - 6 wt%. The post-eruptive Batur magma was cooler (<1100oC) and it is melt more water rich (> 6 wt % H2O). A pressure of 20 kbar is infered from mineral barometry for the Batur magma chamber. Magmatic chamber model is one in which crystals and melt separate from a convecting Batur magma by density differences, resulting in a stratified magma chamber with a homogeneous central zone, a crystal-rich accumulation zone near the walls or base, and a buoyant, melt-rich zone near the top. This is consistent with the estimated magma temperatures and densities: the pre-eruptive BI-1 magma was hoter (1300oC) and more volatile rich (6 wt % H2O) with density 2.25 g/cm3 than the BI-2 magma (1200oC; 4 wt % H2O) in density was higher (2.50 g/cm3). Batur melt characteristics and intensive parameters are consistent with a volatile oversaturation-driven eruption. However, the higher H2O content, high viscosity and low crystal content of the BI-1 magma imply an external eruption trigger.